(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The decriminalization of consensual same-sex relations through the landmark judgment of Navtej Singh Johar v. Union of India (2018) marked a transformative moment in the constitutional history of India. By partially striking down Section 377 of the Indian Penal Code, the Supreme Court recognized the dignity, autonomy, equality, and privacy rights of LGBTQIA+ individuals. However, despite this judicial advancement, the legal recognition of same-sex marriages continues to remain absent in India. The refusal of the Supreme Court in Supriyo @ Supriya Chakraborty v. Union of India (2023) to legalize same-sex marriage under the Special Marriage Act, 1954 has reignited debates concerning constitutional morality, legislative inertia, human rights, and social justice. This article critically examines the continuing struggle for marriage equality in India beyond the decriminalization of homosexuality. The paper explores the historical evolution of LGBTQIA+ rights in India, constitutional protections under Articles 14, 15, 19, and 21, and the role of transformative constitutionalism in shaping queer jurisprudence. It analyses the legal implications of denying marriage rights to same-sex couples, including the denial of inheritance, adoption, succession, insurance, taxation, and social security benefits. Further, the article evaluates the reasoning adopted by the Supreme Court in the 2023 marriage equality judgment and critiques the judiciary’s reluctance to recognize marriage as a fundamental right for queer couples. Comparative legal developments from countries such as the United States, South Africa, Canada, Taiwan, and Nepal are also discussed to understand the global trajectory of marriage equality. The article argues that the denial of marriage equality perpetuates structural discrimination against LGBTQIA+ persons and undermines constitutional guarantees of equality and dignity. It concludes that while Section 377’s partial invalidation was a constitutional milestone, true equality remains incomplete without legal recognition of same-sex unions. Legislative reforms, anti-discrimination frameworks, and inclusive family laws are urgently required to realize substantive equality and human rights for queer communities in India.